Analisis Faktor Profesionalisme Auditor Internal Terhadap Kualitas Laporan Hasil Pemeriksaan pada Inspektorat Kabupaten Cirebon - Adie Irwan Kusumah (Universitas Peradaban, 2015)
Good governance can be realized through effective internal control, as a result of the implementation of financial accountability. Internal control can effectively provide reasonable assurance on adherence, and effectiveness, efficiency and effectiveness in achieving the purpose of the duties and functions of Government Agencies (assurance activities) can give early warning (early warning system) and the effectiveness of risk management in the implementation of the tasks and functions of Government Agencies (anti-corruption activities); and to maintain and improve governance in the implementation of tasks and functions of Government Agencies (consulting activities). The sampling technique used in this study is saturated or census sample is numbered 69 respondents. Data collection technique is to use literature study, observation, questionnaire and documentation study. Analysis of the data on the influence of the independent variables are the professionalism of internal auditors with the dependent variable quality of the internal auditor's report. The results showed that the factors of the professionalism of internal auditors to improve the quality of examination reports of internal auditors in Inspectorate Cirebon including the factor of independence, professional ability factor, the factor of the scope of work, and the internal audit section management factor.